Production and Manufacturing Training of Rosella Processed Product for Women Farmers in Pagung Village, Semen, Kediri - Lisnanti, Ertika Fitri; Setyawan, Fajar; Samudi, Samudi; Wahyu A, Muhammad Junaidi (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary Sciences, 2019)
Dedication for community was performed to increase added value of rosella to prosperous the women farmers in Pagung village, Semen, Kediri. Rosella was sold in dried (not processed product) to middleman in all this time. We expected women farmers find out the way to process rosella into jam, syrup, juice and teabag. Processing of rosella product is expected to prosperous the women farmers in Pagung Village, Semen, Kediri. This dedication for community involves student in community empowerment activities, with intention to implement their knowledge in processing rosella. The training was held in 3 days, on May 16-18, 2019. After the training we also doing mentoring until the community could make the processed product. The participant of this training was 30 women farmers in Pagung Village, Semen. The target of this training is every participant could make rosella processed product properly so it can be traded. Satisfactory results were obtained from this dedication for community, which is held by the team, village administrator and student collaboration. Beside each participant was very enthusiastic, they also become skilled in production of rosella processed product. Each participant has an opportunity to practice directly. This training can increase the knowledge how to manage rosella more economical and have high price.